Influence of Young Children's Life Experiences on Distracting Behaviors: An Example of a Shadowing Teaching Activity - Chen, Dinglin (International Journal of Social Sciences and Public Administration, 2024)
This paper investigates the effect of whether young children have life experience on inhibiting distracted behavior from the perspective of micro scientific collective teaching activities. In this work, Self-administered young children's shadow experience questionnaire was used to distinguish the experimental and control groups through conversation, and the attention level observation recording form and operational definition of distracting behavior were used to conduct experiments on 18 young children in a kindergarten in one kindergarten of city T. T-tests of the experimental data were carried out using SPSS22.0. Under the premise of controlling age, activity plan and other variables, different groups of samples for the number of distracting behaviors all do not show significance (p>0.05), meaning that different groups of samples for the number of distracting behaviors all show consistency, and there is no difference. In conclusion, the samples of different groups do not show significant differences in the number of distracting behaviors. The results indicate the presence or absence of life experience in young children does not have a significant effect on distracting behaviors.